Gaston Bachelard et le rêve de la nuit : quelle méthode pour un « mystère d’ontologie » ? - Pfister , Zoé (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2022)
In Bachelard’s work, night dream, which is an essential topic for psychoanalysis, seems to share the same fate as this method. Like the latter, it is sidelined and depreciated to the benefit of a phenomenology of poetic reverie. This paper, after studying the reasons for which Bachelard neglects night dreams, yet intends to show that these are not totally abandoned to psychoanalysis: a phenomenology of night dream can even be found in some of his texts. We try to highlight it thanks to a part of Binswanger’s work, equally concerned about proposing a phenomenological approach for dreams rather than a psychoanalytic hermeneutics of dream images.